Kondisi Ketenagakerjaan Pekerja Lanjut Usia dan Perubahannya Saat Pandemi COVID-19 di Indonesia Menurut Jenis Pekerjaannya: Analisis Data Sakernas 2021 - Hafizh Meyzar Aqil (Jurnal Ketenagakerjaan, 2023)
Indonesia has entered population aging in the year 2021, referred by the elderly dependent number above 10%. The increase in the number or percentage of elders that still work expectedly can contribute to the economy. However, until the year 2o2o, most elderly workers, still considered informal workers, call into doubt their contribution to the economy. Meanwhile, during the Covid-19 pandemic, informal and elderly workers are among the vulnerable group. This study aims to determine changes related to employment conditions for elderly workers based on the type of work before and during the COVID-19 pandemic in Indonesia. This quantitative research study uses descriptive analysis of data from the National Labor Force Survey (Sakernas) in August 2021. The study resulted that most elderly workers choose to work as independent workers/informal entrepreneurs. In addition, reduced hours worked and average earnings were experienced by all types of jobs, with jobs within the informal sector (informal self-employed, informally paid, and unpaid/family) tending to have the worst outcome. The government is expected to provide assistance during the COVID-19 era for elderly workers, especially informal independent elderly workers who have a significant contribution.